The assessment of awareness and hand hygiene behavior in a selected group of adults - Wiktoria Surman (Kazimierz Wielki University, 2018)
summary Admission Hand washing is the easiest and most effective way to get rid of germs from the hands and preventing their further transmission. Studies have been conducted to determine the degree of bacterial contamination of hands. Objective of the work The aim was to examine the knowledge of a selected group of people aged 17 to 50 years of age with respect to hygiene washing hands and confront it with the selected behavior in this respect. Material and methods Research knowledge on the purity of the hands was carried out at the catering staff, nursing students and students of veterinary school. Diagnostic survey method was used questionnaire survey of copyright. Used for statistical analysis Chi-square test Persona. Results and conclusions The studies have shown varied, but very good level of knowledgeabout hand hygiene and compliance with its men and women from different social groups. However, none of the respondents in practice do not apply fully to the rules in the process of hand hygiene.